Metabolic effects of psychotropic drugs - Gürok, Mehmet Gürkan; Atmaca, Murad (Nova Science Publishers, Inc., 2017)
Obesity in patients with severe mental disorders is reported approximately twice as much as the prevalence of the general population. In this context, metabolic side effects of psychotropic drugs should be taken into consideration when treating patients with any psychiatric disorder. In this chapter, we review metabolic side effects of psychotropic drugs and would like to draw attention to this subject. © 2017 Nova Science Publishers, Inc.
Keywords: Antidepressants; Antipsychotics; Metabolic effects; Psychotropic drugs